Towards a material politics of socio-technical transitions: Navigating decarbonisation pathways in Malmö. (June 2019) - Stripple, Johannes; Bulkeley, Harriet
Abstract: As the politics of climate change shift from the design of international institutions to the pursuit of decarbonisation across multiple sites, researchers are increasingly calling attention to the geography and politics of transitions. We suggest that recent work has so far been limited by its rather incongruous focus on power as a capacity held by individual agents on the basis of the resources which they command, such that the material and relational aspects of socio-technical systems and their dynamics are neglected. In this paper, we bring critical political geographical perspectives to bear on the question of the politics of decarbonisation. Recasting decarbonisation as a matter of political geography then opens up questions of its socio-spatial configuration, its indeterminate and provisional nature as well as the ways in which decarbonisation politics are socio-materially constituted. In Malmö, a city renowned for its attempts to direct urban development towards low carbon futures, we find that decarbonisation is enacted through practices of legibility, demonstration and agreement. These serve to navigate particular junctures and form new socio-material connections and realignments between carbon, capital and infrastructure. We suggest that pathways to decarbonisation are not going to be created by any kind of linear blueprint but through processes that allow them to realign and reorder socio-material relations in new sites and domains across the urban fabric. Highlights: Provides a novel account of scholarship on power and politics in the arena of low carbon transitions. Makes the case for the contribution of perspectives on material politics in shaping our understanding of decarbonisation. Examines how decarbonisation pathways in Malmö are enacted through practices of legibility, demonstration and agreement. Argues that decarbonisation pathways emerge through the realigning of socio-material relations across the urban fabric.